THE STUDY OF THE CREATIVITY IN THE WRITING WORKS OF SHEIKH TAHIR SHUSHY: داهێنان وهنرمەندی دبەرهەمێ شێخ طاهرێ شووشی دا - Shushy, Hamza Tahir (Journal of Duhok University, 2018)
creativity and sophistication in the writings of the Kurdish author and writer of Sheikh Tahir Alshoshi , who is considered as one of the famous religious scholar in the city of Akre city , shows his hard and brilliant work which he left behind in terms of his dimensional writings and technical poetry and material possessions, despite the absence of the modern materials , he didn’t had teacher to teach him calligraphy and decorative arts in his writings , and didn’t enter any session to evolve his talents as is approached nowadays , it was a gift given by Allah to his patience , diligence , hard work and his love to knowledge. What draws attention is the deceased Alshoshi did not last in life for more than forty-five years , he was born in the year (1917) and died (12/12/1962 AD), he spent the eight last years of his life in hospitals between Mosul and Baghdad which were full of sickness and the difficulty of living . Most of these information that we provide now to the readers haven’t seen the light yet and they are published for the first time, I have tried to show his originality and creativity in writing to the next generations, and to show the secrets and innovations, to illustrate his scientific and technical abilities which clarifies general cultural level in the city of Akre during that period. And we have a great hope that this research will be a beginning for new writings and analyzes to show the cultural and creative level of Kurds writers , especially Sheikh Alshoshi who has devoted most of his life and brought his writings to live even when there was no light except the light of the moon , and the extent of their influence and participation in supplying the scientific movement and Islamic knowledge. To obtain all of them on their efforts and the legacy they left for us . We pray to Allah guiding us to service our scientists , writers and historians who have spared no effort to serve their county, and that Allah might make the Paradise their reward.